Effect of the Interposition of Calcium Phosphate Materials on Tendon-Bone Healing During Repair of Chronic Rotator Cuff Tear. (August 2014) - Zhao, Song; Peng, Lingjie; Xie, Guoming; Li, Dingfeng; Zhao, Jinzhong; Ning, Congqin
Background: The current nature of tendon-bone healing after rotator cuff (RC) repair is still the formation of granulation tissue at the tendon-bone interface rather than the formation of fibrocartilage, which is the crucial structure in native tendon insertion and can be observed after knee ligament reconstruction. The interposition of calcium phosphate materials has been found to be able to enhance tendon-bone healing in knee ligament reconstruction. However, whether the interposition of these kinds of materials can enhance tendon-bone healing or even change the current nature of tendon-bone healing after RC repair still needs to be explored. Hypothesis: The interposition of calcium phosphate materials during RC repair would enhance tendon-bone healing or change its current nature of granulation tissue formation into a more favorable process. Study Design: Controlled laboratory study. Methods: A total of 144 male Sprague-Dawley rats underwent unilateral detachment of the supraspinatus tendon, followed by delayed repair after 3 weeks. The animals were allocated into 1 of 3 groups: (1) repair alone, (2) repair with Ca5 (PO4 )2 SiO4 (CPS) bioceramic interposition, or (3) repair with hydroxyapatite (HA) bioceramic interposition at the tendon-bone interface. Animals were sacrificed at 2, 4, or 8 weeks postoperatively, and microcomputed tomography (micro-CT) was used to quantify the new bone formation at the repair site. New fibrocartilage formation and collagen organization at the tendon-bone interface was evaluated by histomorphometric analysis. Biomechanical testing of the supraspinatus tendon-bone complex was performed. Statistical analysis was performed using 1-way analysis of variance. Significance was set at P < .05. Results: The micro-CT analysis demonstrated remarkable osteogenic activity and osteoconductivity to promote new bone formation and ingrowth of CPS and HA bioceramic, with CPS bioceramic showing better results than HA. Histological observations indicated that CPS bioceramic had excellent biocompatibility and biodegradability. At early time points after the RC repair, CPS bioceramic significantly increased the area of fibrocartilage at the tendon-bone interface compared with the control and HA groups. Moreover, CPS and HA bioceramics had significantly improved collagen organization. Biomechanical tests indicated that the CPS and HA groups have greater ultimate load to failure and stiffness than the control group at 4 and 8 weeks, and the CPS specimens exhibited the maximum ultimate load to failure, stiffness, and stress of the healing enthesis. Conclusion: Both CPS and HA bioceramics aid in cell attachment and proliferation and accelerate new bone formation, and CPS bioceramic has a more prominent effect on tendon-to-bone healing. Clinical Relevance: Local application of CPS and HA bioceramic at the tendon-bone interface shows promise in improving healing after rotator cuff tear repair.